If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -54 + -5x = 90 + 7x Solving -54 + -5x = 90 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -54 + -5x + -7x = 90 + 7x + -7x Combine like terms: -5x + -7x = -12x -54 + -12x = 90 + 7x + -7x Combine like terms: 7x + -7x = 0 -54 + -12x = 90 + 0 -54 + -12x = 90 Add '54' to each side of the equation. -54 + 54 + -12x = 90 + 54 Combine like terms: -54 + 54 = 0 0 + -12x = 90 + 54 -12x = 90 + 54 Combine like terms: 90 + 54 = 144 -12x = 144 Divide each side by '-12'. x = -12 Simplifying x = -12
| -6x+24=-4x+4 | | 2(1/3x-12)^2+(5/3x-12)+2=0 | | x^2-21=-21 | | 2(b+2)-(6+b)=-6 | | 83.3x=30 | | 3(3x-4)=24 | | 3/6*8/4*2/3*6/3 | | X^2-5x-120=180 | | (6x^2+36x+28)/(x+5) | | 0.07q+0.7=0.17q-9.5 | | 9-6+u=(27-24)(2)+u | | -13+5h=12 | | 2x+14=5x+5 | | 56-(2x+13)=2(x+9)+x | | 5n+6=-7(5n-6)-6n | | (1/2x-1)^2+(1/2x-1)-72=0 | | 4x+7-6=54x+4 | | 2c^3+2c^2-4c=0 | | 9x^4+15x^3-36x^2-60x=0 | | 7.6p-3.1=42.5 | | 5.2=.04m | | 3(3x-12)=24 | | 13+1x=1 | | 2x+4-5x(x-5)=5x | | 2-6n=-5(4-n) | | -4(-8+2)=-4x-8 | | 2x^4-56x^2+150=0 | | 13x+12= | | -4c-18=-6c-8 | | 2x+10-6x=19-18x+14x-9 | | (3/5)x=15 | | -5/2=0.04m |